Embracing Complexity: Human Rights in Critical Race Feminist Perspective - Lewis, Hope (Columbia Journal of Gender and Law, 2003)
Is feminist human rights scholarship prepared to address the current crisis in international law and politics? Globalization, the reassertion of deep cultural divides, war, armed conflict, terrorism,’ the HIV/AIDS pandemic, the appalling economic status of women in the Global South, desperate flows of migrants willing to risk death for economic opportunity, violence against women who resist traditional (or modern) behavioral norms, and violence against women for simply being women-all seem to indicate increasing complexity in the challenges facing feminist legal scholarship. If international feminist approaches to human rights exist only as part of a static, hegemonic, and imperialist framework, they would indeed be unable to engage the contemporary needs and aspirations of women cross-culturally. In my view, however, the voices of “women of all colors” have enriched the objectives and norms of feminist human rights scholarship and have embraced complex challenges from the beginning. Nonetheless, the voices of women at the margins-women of color and Third World women among them-have too often been rejected out of hand, ignored, or otherwise made invisible. Critical Race Feminist and other multicultural approaches to legal scholarship attempt continually to recenter such voices and unearth their experiences and perspectives in the search for effective social justice strategies. As we collectively reflect on the successes and challenges facing feminist scholarship in this dangerous and critical time, the particularities of culture, race, nation, and other forms of identity must be fully recognized as important aspects of feminist human rights discourse. This brief essay argues, therefore, that Critical Race Feminist and other multicultural approaches will make important, although ambivalent, contributions to the overall international human rights agenda.